Modeling of Carbon Dioxide Absorption into Aqueous Ammonia in a Wetted Wall Column - Chiu, C.H.; Ghosh, Ujjal (UTP, 2012)
Carbon dioxide absorption process using an ammonia solution provides many advantages including higher absorption capacity, no degradation and lower regeneration energy requirement. In this paper, a mathematical model is developed based on mass and momentum balance and used to investigate the relationship of partial pressure of carbon dioxide, temperature, and vapour-liquid contact area to separation of carbon dioxide from flue gas through wetted wall column. The model is simplified based on the assumption that the CO2 absorption into aqueous ammonia is a pseudo-first-order reaction. Variation of CO2 molar flux with partial pressure of CO2 and temperature is discussed and a comparison is performed with experimental data from literature. Variation of CO2 molar flux is also shown with gas-liquid contact area.